Seed‐competent high‐molecular‐weight tau species accumulates in the cerebrospinal fluid of Alzheimer's disease mouse model and human patients. Issue 3 (3rd August 2016) - Takeda, Shuko; Commins, Caitlin; DeVos, Sarah L.; Nobuhara, Chloe K.; Wegmann, Susanne; Roe, Allyson D.; Costantino, Isabel; Fan, Zhanyun; Nicholls, Samantha B.; Sherman, Alexis E.; Trisini Lipsanopoulos, Ana T.; Scherzer, Clemens R.; et al.
Abstract : Objective: Cerebrospinal fluid (CSF) tau is an excellent surrogate marker for assessing neuropathological changes that occur in Alzheimer's disease (AD) patients. However, whether the elevated tau in AD CSF is just a marker of neurodegeneration or, in fact, a part of the disease process is uncertain. Moreover, it is unknown how CSF tau relates to the recently described soluble high‐molecular‐weight (HMW) species that is found in the postmortem AD brain and can be taken up by neurons and seed aggregates. Methods: We have examined seeding and uptake properties of brain extracellular tau from various sources, including interstitial fluid (ISF) and CSF from an AD transgenic mouse model and postmortem ventricular and antemortem lumbar CSF from AD patients. Results: We found that brain ISF and CSF tau from the AD mouse model can be taken up by cells and induce intracellular aggregates. Ventricular CSF from AD patients contained a rare HMW tau species that exerted a higher seeding activity. Notably, the HMW tau species was also detected in lumbar CSF from AD patients, and its levels were significantly elevated compared to control subjects. HMW tau derived from CSF of AD patients was seed competent in vitro. Interpretation: These findings suggest that CSF from an AD brain contains potentially bioactive HMW tau species, giving new insights into the role of CSF tau and biomarker development for AD. Ann Neurol 2016;80:355–367